2020
DOI: 10.1186/s12884-020-03367-z
|View full text |Cite
|
Sign up to set email alerts
|

Fear of childbirth among pregnant women attending antenatal care in Arba Minch town, southern Ethiopia: a cross-sectional study

Abstract: Background Fear of childbirth is one of the life challenges the women encounter during pregnancy. It is an important source of distress for the women and their families and also increases the odds of obstetric complications during childbirth. The aim of this study was to assess the magnitude of fear of childbirth and associated factors among pregnant women attending antenatal care at public health facilities in Arba Minch town, southern Ethiopia. Methods Institution-based cross-sectional study was carried ou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 32 publications
(28 reference statements)
5
31
0
Order By: Relevance
“…in Ireland, 6.1% in Iran, 8% in Kenya, 20.8% in Turkey and 24.5% in Ethiopia [41][42][43][44][45][46]. It seems di cult to compare the incidence of FOC cross countries due to different measures and de nitions.…”
Section: Discussionmentioning
confidence: 99%
“…in Ireland, 6.1% in Iran, 8% in Kenya, 20.8% in Turkey and 24.5% in Ethiopia [41][42][43][44][45][46]. It seems di cult to compare the incidence of FOC cross countries due to different measures and de nitions.…”
Section: Discussionmentioning
confidence: 99%
“…is might be due to the depletion of iron because of frequent pregnancies and loss of blood during pregnancy, delivery, and a postpartum period where women who become pregnant in a short time before replenishing the lost blood are susceptible to anemia. Women who give birth more frequently can face stress and fear that in turn prevent them from eating adequate food which in turn leads to anemia [36].…”
Section: Discussionmentioning
confidence: 99%
“…The scale included four domains: fear of fetal health; fear of losing control during childbirth; fear of childbirth pain; fear of medical intervention and the hospital environment. CAQ total scores were categorized as none (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), mild (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), moderate (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51) and severe (52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64). Wei wand her colleagues translated the scale into Chines...…”
Section: Fear Of Childbirthmentioning
confidence: 99%
“…Our data showed that FOC occurred in 67% of pregnancies, and 2.2% of participants experienced severe FOC. Several studies reported the following rates of severe FOC: 5% in Australia, 5.3% in Ireland, 6.1% in Iran, 8% in Kenya, 20.8% in Turkey and 24.5% in Ethiopia [43][44][45][46][47][48]. It is difficult to compare the incidence of FOC across countries due to differences in the measures and definitions used.…”
Section: The Prevalence Of Focmentioning
confidence: 99%